ChemInform Abstract: Bismuth Phosphate: A Novel Cathode Material Based on Conversion Reaction for Lithium‐Ion Batteries. Issue 47 (4th November 2013) - Hu, Benan; Wang, Xianyou; Wei, Qiliang; Shu, Hongbo; Yang, Xiukang; Bai, Yansong; Wu, Hao; Song, Yunfeng; Liu, Li
Abstract Hexagonal BiPO4 is precipitated from a solution of Bi(NO3)3 in 10 wt.% aq.